Verbal and nonverbal correspondence in science: a discussion about research integrity (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
The types of fraud more frequently observed in the scientific context involve the fabrication or falsification of data and plagiarism, practices associated with the verbal behavior of the offender researchers. The purpose of this study was to analyze and discuss some aspects of the scientific honesty and dishonesty in terms of the literature on do-say correspondence. For this, experimental evidence produced in the verbal correspondence area was used to interpret some data from the literature on scientific fraud. The analysis suggests that fabrication or falsification of data and plagiarism could be examples of distorted tacts, whose occurrences may be associated with cultural practices that favor the dissemination of positive results or that inflate the reinforcing value of scientific publications. On the other hand, strategies tested experimentally by the verbal correspondence area, such as monitoring and checking correspondence of the report, can contribute to honesty in the scientific context.
Keywords: research integrity; verbal behavior; do-say correspondence; scientific misconduct